Negative regulation of CDC42 expression and cell cycle progression by miR-29a in breast cancer - Zhang Mingliang; Guo Wei; Qian Jun; Wang Benzhong (Open Medicine, 2016)
The inhibitory role of microRNA-29a (miR-29a) has been assessed in breast cancer cells. Herein, we analyze the underlying mechanisms of its role in cell cycle progression in breast cancer cells.